2003
DOI: 10.1111/j.1744-7429.2003.tb00270.x
|View full text |Cite
|
Sign up to set email alerts
|

Benthic Community Structure and Invertebrate Drift in a Pacific Island Stream, Kosrae, Micronesia1

Abstract: Tropical Pacific island streams have poorly understood communities that deserve scientific attention. We examined benthic macroinvertebrates and fishes of the Inem River on Kosrae, Federated States of Micronesia. Larval chironomids, lepidopterans, odonates, and freshwater shrimps dominated the benthos and drift. Diel periodicity in drift was not evident. Nine fishes, two shrimps, and one snail species were identified. Kosrae's stream fauna appears even more depauperate than other Pacific high islands, possible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(9 citation statements)
references
References 16 publications
0
8
0
1
Order By: Relevance
“…This started with baseline assessment of the forest resource (Petteys et al 1993) and assessment of values and recommendations for creation of forest reserves (Devoe 1993). Subsequent research has included community structure (Cole et al 1999;Allen et al 2003;Ewel et al 2003;March et al 2003), productivity and growth (Ewel et al 1998a;Devoe and Cole 1998;Allen et al 2000;Pinzón et al 2003;Allen et al 2005;Krauss et al 2006), carbon fluxes (Gleason and Ewel 2002;Ewel 2004, 2005), organic matter dynamics (Gleason et al 2003), sedimentation , disturbance (Ewel et al 1998b;Allen et al 2001;Hauff et al 2006) and wetland valuation (Naylor and Drew 1998;Naylor et al 2002;Drew et al 2005). Other countries in the region are very depauperate of such detailed and interconnected scientific ecological work, and in many none has occurred at all.…”
Section: Ecological Characteristics Populations Communitiesmentioning
confidence: 96%
“…This started with baseline assessment of the forest resource (Petteys et al 1993) and assessment of values and recommendations for creation of forest reserves (Devoe 1993). Subsequent research has included community structure (Cole et al 1999;Allen et al 2003;Ewel et al 2003;March et al 2003), productivity and growth (Ewel et al 1998a;Devoe and Cole 1998;Allen et al 2000;Pinzón et al 2003;Allen et al 2005;Krauss et al 2006), carbon fluxes (Gleason and Ewel 2002;Ewel 2004, 2005), organic matter dynamics (Gleason et al 2003), sedimentation , disturbance (Ewel et al 1998b;Allen et al 2001;Hauff et al 2006) and wetland valuation (Naylor and Drew 1998;Naylor et al 2002;Drew et al 2005). Other countries in the region are very depauperate of such detailed and interconnected scientific ecological work, and in many none has occurred at all.…”
Section: Ecological Characteristics Populations Communitiesmentioning
confidence: 96%
“…As juveniles or postlarvae, they migrate upstream considerable distances over steep terrain and climb up high waterfalls. These taxa are especially well adapted for completing major periods of their life histories in tropical stream drainages, where they play essential roles in aquatic food webs (Covich and McDowell 1996, Crowl et al 2001, March et al 2003a, Williams 2002). These life-history characteristics have resulted in a significant number of shared common genera of fishes, decapods, and gastropods in many streams throughout the tropical Pacific and Caribbean (Fievet et al 2001, Leberer and Nelson 2001, Debrot 2003, March et al 2003b.…”
Section: Geologic and Biological Processesmentioning
confidence: 99%
“…While 31 families and 53 genera were recorded in Gorgona, 18 families and 27 genera were recorded in Isla del Caño (Springer, 2004), and 40 families (7 orders, no genera-level reports) in Coiba (Boyero & Bailey, 2001). In more remote oceanic islands in the mid Pacific, such as Kosrae in Micronesia, the richness is significantly lower (3 orders and 3 families: March et al, 2003;Benstead et al, 2009) than in continental islands in the Tropical Eastern Pacific.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been found that island origin, isolation, size, and age, as well as ocean currents and climate change, are important influences at a regional scale (e.g. March, Benstead, Pringle & Luckymis, 2003;Craig, 2003;Benbow, McIntosh, Burky & Way, 2005;Covich, 2006;Benstead, March, Pringle, Ewel & Short, 2009). At the basin scale, stream order and invasion by introduced species are major filters (Englund, 1999).…”
mentioning
confidence: 99%